2016
DOI: 10.1136/bcr-2016-216150
|View full text |Cite
|
Sign up to set email alerts
|

A curious cause of appendicitis

Abstract: A previously healthy 10-year-old boy presented to the emergency department with central abdominal pain, loose stool and vomiting. He was diagnosed with gastroenteritis, but was well enough to be discharged. The next day he reattended with ongoing diarrhoea and vomiting, with the pain now localised to the right iliac fossa (RIF). Acute appendicitis was suspected, and he was taken for laparoscopic appendicectomy. At surgery, a gangrenous appendix was found, with pus extending from the pelvis up to the liver. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…This case adds to a small body of literature recognizing an association between enteric bacterial pathogens Salmonella sp. [ 4 , 5 , 6 , 7 , 8 ] and Campylobacter sp. [ 6 , 7 ] and acute appendicitis, thus serving as a rare example of a common surgical emergency.…”
Section: Discussionmentioning
confidence: 99%
“…This case adds to a small body of literature recognizing an association between enteric bacterial pathogens Salmonella sp. [ 4 , 5 , 6 , 7 , 8 ] and Campylobacter sp. [ 6 , 7 ] and acute appendicitis, thus serving as a rare example of a common surgical emergency.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of our patient S almonella bredeney was also isolated in his stool sample. Appendicitis associated with non-typhoidal S almonella infection is also described 16 17. There were no measles-specific histological features in the appendix specimen.…”
Section: Discussionmentioning
confidence: 98%
“…Invasive systemic disease such as bacteraemia is a known clinical manifestation in typhoidal salmonella infections but uncommon in non-typhoidal salmonella infections which typically manifests as self-limiting gastroenteritis [ 4 ]. Appendicitis is a rare form of presentation of acute abdomen in Salmonella infections [ 5 ]. Van Noyen et al [ 6 ] showed that only an estimated 8% of culture-proven bacterial enteritis had histologically proven appendicitis due to Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…Van Noyen et al [ 6 ] showed that only an estimated 8% of culture-proven bacterial enteritis had histologically proven appendicitis due to Salmonella. Two mechanisms on how Salmonella causes appendicitis have been described; either by direct invasion or via blood or lymphatics resulting in inflammation [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation